Oblivionism Forgetting and Forgetfulness in Modern Science - Dimbath, Oliver (Brill, 2022)
The book offers a fundamental view on the problem of forgetting in sociology in general and within sociology of knowledge. Furthermore it focuses - as a case study - on the field of modern science. With recourse to the term ,oblivionism', originally introduced with ironic-critical intent by the german romance scholar Harald Weinrich, it analyzes the fundamental and multifaceted problem of the loss of knowledge in the field of science. A declarative-reflective, an incorporated-practical and an objectified-technical memory motif is at the centre. These form the basis for the development of the three forms of forgetting that are also central to modern science: forgetfulness, wanting to forget and, ultimately, making one forget.